Kemampuan Berbahasa Bali pada Kalangan Remaja di Desa Pakraman Peraupan Denpasar - I Gede Sudiarta (UHN IGB Sugriwa Denpasar, 2015)
In globalization era, language has an important place to build teenager orientation. Language could show someone and nation characteristic. Language is not only as a communication, but also as a processof human thinking to comprehend something objectively and imaginatively. It could show every aspect of human life. In addition, without language people will be noiseless and will die in the silent. One way to conserve Balinese language is increase teenager’s interst. According to the explanation above, the problems in this research can be formulated as follows ; 1) how is the Balinese teenager’s ability in using Balinese language in Peraupan Denpasar Village? 2) what are the factors that affect Balinese teenager’s ability in using Balinese language in Peraupan Denpasar village? 3) what are the efforts that can be used to increase Balinese teenager’s ability in using Balinese language in Peraupan Denpasar village?. Theories that was used in this research were sociolinguistics theory, language attitude theory, social changes theory and learning motivation theory. This research used some data collection techniques, such as observation, interview and literature. Data which have been collected was proceed and analysed by using qualitative descriptive method. The result of this research showed that as follows; 1) Balinese teenager’s ability in using Balinese in Peraupan Denpasar village is still low if it is connected to sor singgih, 2) the factors that that can affect Balinese teenager’s ability in using Balinese language in Peraupan Denpasar village are technology, environment, and the difficulties of Balinese language also less of tools and infrastructure, 3) the efforts that could be done to solve the problem are making a contest, doing pasraman activity, using Balinese language (sor singgih) in meeting, upgrading parents role, an upgrading school role.